Value Added Analysis And Development Strategies For Special Coffee Processing Business in Wih Pesam District, Bener Meriah Regency, Aceh Province - Asrah FM. Harahap (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2022)
This study aims to analyze the amount of added value and profits obtained by the owner in the Specialty Coffee processing business and to determine product development strategies in Wih Pesam District, Bener Meriah Regency. This research was conducted in September 2021. The determination of the research area was based on the consideration that, in Wih Pesam District, there is Arabica Coffee processing into Specialty Coffee. Respondents in this study were business owners of Arabica Coffee Processing into Specialty Coffee. Determination of the sample is done intentionally (purposive). The analysis used is a profit-loss calculation, added value, and SWOT analysis. The results show that the business of processing Arabica Coffee into Specialty Coffee provides a profit of Rp. 2,843,798 /Once the production process for one month and creates an added value of Rp. 145,449/ kg per kg of raw materials. The ratio of added value to product value is 72.63%, meaning that for every Rp 100 product value, an added value of Rp 72 will be obtained. The added value indicates a high value. The strategy that will be used is the Aggressive Strategy. This aggressive strategy focuses more on SO (Strenght-Opportunities) by using strengths to take advantage of existing opportunities, where these businesses have opportunities and strengths so they can take advantage of existing opportunities. From the company's internal perspective, strengths are greater than weaknesses. It can be seen from the calculation results, namely, the strength value is 3.95 and the weakness value is 1.45. Then from an external perspective, opportunities are greater than threats, it can be seen from the calculation results, namely, the opportunity value is 3.24 and the weakness value is 2.3.